TRANSFORMASI TENAGA KERJA WANITA DI SEKTOR AGROINDUSTRI TEMBAKAU - Julian Adam Ridjal (University of Jember, 2011)
This research was to know factors of woman labor transformation to tobacco agroindustry in Jember Regency by purposive method. Interaction of environmental factors (work) significantly affect the transformation of woman labor decisions of the agricultural sector (as agricultural laborers) to tobacco agroindustry (as a factory employee) of -0.98, and direct effect of the transformation on the level of income of 0.502 and significant. The biggest influence is given by the age of 2 lines, the interaction effect of age to the environment (work) through the transformation of 0,058 with the direction of the negative relationship. Keywords : tranformation, tobacco agroindustry,